WAYS TO ORGANIZE THE PEDAGOGICAL PROCESS OF TEACHING CHILDREN WITH DISABILITIES IN SECONDARY SCHOOLS - Nishonova Klara (Galaxy International Interdisciplinary Research Journal, 2021)
Inclusive education is a public policy, a flexible and individualized care system for sick children with disabilities or other reasons who need special care, and is an inclusive, innovative type of education that provides equal treatment for all children.To treat all children equally, regardless of nationality, race, body color, social origin, family status in society, source, material and spiritual condition, physical or mental development, to give them every opportunity appreciation is an education that involves development.